Determinants of producers’ choice of wine grape cultivars in the South African wine industry - Musango, Josephine Kaviti (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MAgricAdmin (Agricultural Economics))--University of Stellenbosch, 2005.